Water storage changes as a marker for base flow generation processes in a tropical humid basement catchment (Benin): Insights from hybrid gravimetry. Issue 10 (23rd October 2015) - Hector, Basile; Séguis, Luc; Hinderer, Jacques; Cohard, Jean‐Martial; Wubda, Maxime; Descloitres, Marc; Benarrosh, Nathalie; Boy, Jean‐Paul
Abstract: In basement catchments of subhumid West Africa, base flow is the main component of annual streamflow. However, the important heterogeneity of lithology hinders the understanding of base flow generation processes. Since these processes are linked with water storage changes (WSCs) across the catchment, we propose the use of hybrid gravity data in addition to neutron probe‐derived water content and water levels to monitor spatiotemporal WSC of a typical crystalline basement headwater catchment (16 ha) in Benin. WSC behaviors are shown to provide insights into hydrological processes in terms of water redistribution toward the catchment outlet. Hybrid gravimetry produces gravity change observations from time‐lapse microgravity surveys coupled with gravity changes monitored at a base station using a superconducting gravimeter and/or an absolute gravimeter. A dense microgravity campaign (70 surveys of 14 stations) covering three contrasted years was set up with a rigorous protocol, leading to low uncertainties (<2.5 μGal) on station gravity determinations (with respect to the network reference station). Empirical orthogonal function analyses of both gravity changes and WSCs from neutron probe data show similar spatial patterns in the seasonal signal. Areas where storage and water table show a capping behavior (when data reach a plateau during the wet season), suggesting threshold‐governed fast subsurface redistribution, are identified. This observed storage dynamics, together with geological structures investigated by electrical resistivity tomography and drill log analysis, make it possible to derive a conceptual model for the catchment hydrology. Key Points: Hybrid gravity and neutron probe data show similar space‐time storage patterns Storage change patterns are related to lithology derived from geophysics and drill logs Storage change observations helped to derive a conceptual model for the catchment hydrology